The Linguistic-Cultural Image of the Time Based on Metaphors of Daily and Annual Cycle Included in Funeral Inscriptions of Village Cemeteries (Example of Selected Villages of Podkarpacie and Małopolska Regions) - Herchel, Małgorzata (Starość i młodość w literaturze i kulturze, 2016)
The deceased person, whose presence is constituted in funeral inscriptions by presentation of hisname, surname and other information such as his achievements, is a crucial component of this sort oftexts. The time seems to appear as equally important element of the inscriptions, which is a result of thefact that the existence of the dead person is immersed in the real historical time. Its linguistic image includedin folk funeral inscriptions creates multivariate occurrence. Numerous groups of inscriptions usemetaphors connected with the daily and annual cycle. These inscriptions significantly create the linguisticimage of life and death and express its typical folk notion.